PERTUMBUHAN DAN PRODUKSI CABAI RAWIT (Capsicum frutescens L.) PADA BERBAGAI KONSENTRASI TRICHODERMA DAN BIOCHAR TEMPURUNG KELAPA - Andani, Selvi; Subaedah, St.; Edy, Edy (Percetakan Umi Toaha Makassar, 2025)
This study aimed to: 1) analyze the growth and yield of chili pepper (Capsicum frutescens L.) under various concentrations of Trichoderma; 2) analyze the growth and yield of chili pepper under different application rates of coconut shell biochar; and 3) examine the interaction effects between Trichoderma and coconut shell biochar on the growth and yield of chili pepper. The research was conducted at P4S (Self-help Agricultural and Rural Training Center), Lampoko Village, Barebbo District, Bone Regency, South Sulawesi Province, from May to August 2025. This study employed an experimental design with a quantitative approach using a factorial randomized block design (RBD). The combination of the two treatments resulted in 9 treatment combinations, each replicated three times, yielding 27 experimental units. The results showed that the application of Trichoderma up to 15 g/plant and coconut shell biochar up to 20 tons/ha significantly improved the growth and yield of chili pepper. The combination of both treatments gave the best effect, where the interaction between Trichoderma and biochar produced more optimal vegetative growth and higher fruit yield compared to single treatments. This demonstrates the synergy between Trichoderma, which acts as a growth promoter through hormone production and enhanced nutrient uptake, and biochar, which functions as a soil conditioner that improves water retention and nutrient availability for plants